Resource partitioning between two young-of-year cownose rays Rhinoptera bonasus and R. brasiliensis within a communal nursery inferred by trophic biomarkers - Rangel, Bianca de Sousa; Hussey, Nigel E.; Gomes, Aline D.; Rodrigues, Alexandre [UNESP]; Martinelli, Luiz A.; Moreira, Renata Guinnaraes (Wiley-Blackwell, 2019)
Although interspecific trophic interactions plays a principal role within elasmobranch communal nurseries, little is known over variation in foraging strategies adopted by young-of-year of sympatric species. To test the hypothesis of dietary resource partitioning between batoids within a communal nursery, we investigated two cownose ray species, Rhinoptera bonasus and R. brasiliensis, which occur in heterospecific groups, a strategy predicted to increase survival and foraging success. Using two biochemical tracers, fatty acids (FA) and stable isotopes (delta N-15 and delta C-13), the combined effects of maternal investment and the formation of heterospecific groups implying competition for, or partitioning of available food resources were investigated. Through univariate and multivariate analyses of biochemical tracers in several tissues (fin clip, muscle, liver, red blood cells; RBC) and plasma, our results revealed significant interspecific differences in tracers between the two species. Total FAs ( n-ary sumation saturated FA, n-ary sumation monounsaturated FA and n-ary sumation polyunsaturated FA) and trophic biomarkers (i.e., docosahexaenoic acid, arachidonic acid, oleic acid and delta N-15) were the principle tracers responsible for the differences detected. These data revealed that R. brasiliensis was less enriched in physiologically important essential FAs than R. bonasus. Our findings suggest that these congeneric species differ in maternal investment strategy and moderately partition food resources over relatively fine spatial scales within a single nursery habitat to limit competition. These results provide further knowledge on the foraging strategies adopted by batoids in communal nursery areas, information that is required for improving spatial conservation and management planning.
Keywords: elasmobranch; fatty acids; life history strategy; maternal investment; stable isotopes; trophic ecology